Digital Public Opinion and Infrastructure Framing in the Bandar Lampung Cable Car ProjectAccount@Lampung - Naning Kirani; Fitri Yanti; Nadya Amalia Nasution (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study aims to analyze the perceptions of Bandar Lampung City residents toward news coverage of the cable car project on the Instagram account @lampung. The development of digital communication technology has transformed social media, particularly Instagram, into a digital public sphere that shapes public opinion regarding local government development policies. This research employed a qualitative descriptive approach using a netnographic method through online observation and screen capture techniques. The data consisted of public comments on three posts related to the cable car project published between February and July 2025, which were classified into positive, negative, and neutral perceptions. The findings indicate that public perception was predominantly negative, accounting for 89.9% of the total comments. In the post with the highest level of interaction (May 23, 2025), there were 4,310 negative comments (93.3%), 45 positive comments (1.0%), and 312 neutral comments (6.7%). Negative perceptions were driven by concerns regarding inappropriate development priorities, potential environmental impacts, lack of project transparency, and low public trust in the government. Meanwhile, positive perceptions emerged from expectations of increased tourism, regional economic growth, and the strengthening of Bandar Lampung City’s image.These findings reinforce the relevance of framing and agenda-setting theories in explaining the dynamics of public opinion on social media and provide practical implications for local government public communication strategies in the digital era.